Heterodyning effect in composites bond inspection - (:unkn) unknown (DEStech Publications, 2017)
With daily increase of application composite materials in commercial and military aircrafts, longevity of composite bonds has become a substantial factor in aerospace industry. Although tremendous amount of research has been conducted on monitoring the integrity of composite bonds, developing new structural health monitoring (SHM) techniques for evaluating bond strength could be essential. In this study, heterodyning method is implemented for exploring bond strength and detecting delamination in composite materials. Heterodyne effect may be utilized for the evaluation of debonded area when the linear characteristics of the system changes to nonlinear. The light contact in the bonding zone can result in this conversion from linear to nonlinear behavior. The nonlinear system responds to two appropriate excitation frequencies with new frequencies. For some nonlinear systems, the output has these new frequencies at the subtraction and summation of excitation frequencies. This is called heterodyne effect. This experimental setup was designed to detect debonding in a composite coupon. In the experiment, two composite coupons are manufactured and bonded together by using film adhesive. To create a 2-inch-long debonding, no adhesive was applied in the left side of the bonded coupons. Three piezoelectric disks were attached to the bonded coupons while the middle disk acting as the exciter. The objective of the experiment was to study the alteration of the signals received by the piezoelectric disks attached to the opposite ends due to nonlinear behavior of the structure. The experimental setup was designed for the investigation of undesirable bonding conditions. Since the method evaluates the bond strength by detection of the changes of linear characteristics of the system to nonlinear, there is no need for baseline data. Results show that the proposed method can be used effectively for the composite bond inspection purposes.